1997
DOI: 10.1002/(sici)1097-4628(19970509)64:6<1235::aid-app25>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Tensile property of modified hydroxyl-terminated polybutadiene-based polyurethanes

Abstract: Modified hydroxyl-terminated polybutadiene (HTPB)-based polyurethanes (PUs) were prepared by three different processes: crosslinkage of the soft segment, complexation of the hard segment, and the interpenetrating network (IPN). Crosslinked PU films were prepared by the addition of a crosslinking agent of divinylbenzene (DVB) to the 4,4 -dicyclohexylmethane diisocyanate (H 12 MDI) and 1,4-butanediol (1,4-BD)-based PUs. The ionic polymer was prepared by adding N-methyldiethanolamine (MDEA), which possesses terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Cabasso et al added poly (vinylpyrrolidone) to polysulfone solution and found that the tensile strength of the polysulfone hollow fiber was decreased. Huang et al have studied the effect of hydroxyl‐terminated polybutadiene‐based polyurethanes to improve the mechanical properties of polysulfone membranes. Lai et al have concluded that the presence of nonionic surfactants in a polymer casting solution could improve the mechanical properties of prepared membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Cabasso et al added poly (vinylpyrrolidone) to polysulfone solution and found that the tensile strength of the polysulfone hollow fiber was decreased. Huang et al have studied the effect of hydroxyl‐terminated polybutadiene‐based polyurethanes to improve the mechanical properties of polysulfone membranes. Lai et al have concluded that the presence of nonionic surfactants in a polymer casting solution could improve the mechanical properties of prepared membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Oligomeric hydroxy‐terminated polybutadienes (HTPB) can potentially be used as a polyol component in the synthesis of more hydrophobic polyurethanes . HTPBs are also commercially available products used in composite propellants, adhesives, sealants, high‐quality binders for rubber crumb, potting materials and in electrical isolation, and gas separation equipment .…”
Section: Introductionmentioning
confidence: 99%
“…If the performance of membranes was improved modestly so as to exhibit either the pervaporation total flux of 0.15 kg m −2 h −1 or selectivity of 10.3 for ethanol to water. By affinity, rubbery polymers are the most suitable material for hydrophobic/organophilic pervaporation separation; namely polybutadiene,5 terpolymer ethene‐propene‐diene (EPDM),6 poly(ether block amide) (PEBA),7, 8 polyviniylidene fluoride,9 and the most frequent is polydimethylsiloxane 10–15…”
Section: Introductionmentioning
confidence: 99%